The relationship between parental health literacy and primary school students’ anthropometric measurements and general health status - Elif Uner Asil; Ozcan Aygun; Alime Duman; Nazli Gungor (BMC Pediatrics)
Abstract Background Parental health literacy plays a critical role in children’s health and development. This study was conducted to reveal the relationship between parents’ health literacy level and anthropometric measurements and general health status of primary school students. Methods Power analysis was performed to determine the sample size of the study and 681 children and their parents in 2 primary schools were included in the study. Data were collected using the socio-demographic data form, the student follow-up form, and the short form of the European Health Literacy Scale. The data collection forms were sent to the parents together with the students, and the anthropometric measurements of the children were carried out in an office set up in the school in which they were located. Chi-square test and binary logistic regression analysis were used to analyze the data. Results Parental health literacy was found to be adequate. Statistically significant relationships were found between parental health literacy and factors such as educational level, marital status, general health status of children, and preferences for access to health services (p < 0.05). Conclusions Parents with higher education levels, who positively evaluated their own and their children’s health status and whose children did not have oral and dental health problems had higher levels of health literacy. In this direction, it is recommended to develop special training programs for other parents to increase health literacy.